GESTÃO E AVALIAÇÃO EDUCACIONAL NA ESCOLA DE EDUCAÇÃO BÁSICA - Jacqueline Lima Honda; Elianeth Dias Kanthack Hernandes (Universidade do Oeste Paulista, 2012)
This research has been conducted with the objective of identifying the similarities and the differences between the school management system proposed by the government and the school management system applied on a daily basis by the school management team. This management team is composed by the school principal, the coordinator teacher, and the educational supervisor of a school in the inner state of Sao Paulo. Data is being collected researching the references already existed about the school management system, documents and files of the school, and by an interview with the management team. It is expected that this research will identify the close and the distant aspects between the evaluation of the management team about itself and the evaluation conducted by the school in the process of educational evaluations. The data obtained through this research job is being analyzed considering its quality aspects.